PENGARUH KUALITAS PRODUK DAN SDM TERHADAP STRATEGI PEMASARAN GUNA MENINGKATKAN FEE BASED INCOME - Kadek Adhy Suryadhyantha (Universitas Pendidikan Nasional, 2013)
The purpose of this study were 1) To analyze the effect of product quality to increasefee based income, 2) To analyze the effect of the quality of human resources (HR) to increasefee based income, 3) To analyze the effect of marketing strategies to increase fee basedincome.Respondents of this study were employees of Bank BNI 46 Main Branch Office Renon,amounting to 199 people. Collecting data in this study using a questionnaire containing 18questions, each question using 10 alternative answers. Analysis of the data used to answerthe research questions and test hypotheses influence the quality of product, quality of humanresources and marketing strategies toward fee-based statistical method is used StructuralEquation Modeling (SEM) with AMOS software version 20.The results showed that: 1) the variable quality of the product and the variable feebased income awakened by a strong theoretical basis and the results showed that there ispositive and significant variable fee based income variables 2) the quality of humanresources and the variable fee based income has done research with collect data related tothese variables and have been analyzed by means of SEM analysis with the results of thestudy indicate that there is a positive and significant effect of the variable quality of humanresources to variable fee based income, 3) there is a positive and significant impactmarketing strategy variable to variable fee based income.Keywords: quality of product, quality of human resources, marketing strategies and feebased income